Patient contributions during primary care consultations for hypertension after self-reporting via a mobile phone self-management support system. (2nd January 2018) - Bengtsson, Ulrika; Kjellgren, Karin; Hallberg, Inger; Lundin, Mona; Mäkitalo, Åsa
Abstract: Objective: This paper reports on how the clinical consultation in primary care is performed under the new premises of patients' daily self-reporting and self-generation of data. The aim was to explore and describe the structure, topic initiation and patients' contributions in follow-up consultations after eight weeks of self-reporting through a mobile phone-based hypertension self-management support system. Design: A qualitative, explorative study design was used, examining 20 audio- ( n = 10) and video-recorded ( n = 10) follow-up consultations in primary care hypertension management, through interaction analysis. Clinical trials registry: ClinicalTrials.gov NCT01510301. Setting: Four primary health care centers in Sweden. Subjects: Patients with hypertension ( n = 20) and their health care professional ( n = 7). Results: The consultations comprised three phases: opening, examination and closing. The most common topic was blood pressure (BP) put in relation to self-reported variables, for example, physical activity and stress. Topic initiation was distributed symmetrically between parties and BP talk was lifestyle-centered. The patients' contributed to the interpretation of BP values by connecting them to specific occasions, providing insights to the link between BP measurements and everyday life activities. Conclusion: Patients' contribution through interpretations of BP values to specific situations in their own lives brought on consultations where the patient as a person in context became salient. Further, the patients' and health care professionals' equal contribution during the consultations showed actively involved patients. The mobile phone-based self-management support system can thus be used to support patient involvement in consultations with a person-centered approach in primary care hypertension management Key points: The clinical consultation is important to provide opportunities for patients to gain understanding of factors affecting high blood pressure, and for health care professionals to motivate and promote changes in life-style. This study shows that self-reporting as base for follow-up consultations in primary care hypertension management can support patients and professionals to equal participation in clinical consultations. Self-reporting combined with increased patient–health care professional interaction during follow-up consultations can support patients in understanding the blood pressure value in relation to their daily life. These findings implicate that the interactive mobile phone self-management support system has potential to support current transformations of patients as recipients of primary care, to being actively involved in their own health.